Perspectiva psicosocial del acoso laboral de las trabajadoras del área de gestión humana de una empresa minera del departamento de La Guajira. (2021)
This project addresses the problem of workplace harassment in workers of a mining company in the department of La Guajira with the aim of knowing the psychosocial perspectives of workplace harassment that workers in the human management area have in the mining company of the department of La Guajira. An interview was implemented with a sample of 10 workers from the human resources area of the minare company, where workplace harassment was detected and their opinion on workplace harassment, its consequence in the workplace and psychological, especially how it affects performance and climate labor.